DNA methylation in the wild: epigenetic transgenerational inheritance can mediate adaptation in clones of wild strawberry (Fragaria vesca) - Sammarco, Iris; Díez Rodríguez, Bárbara; Galanti, Dario; Nunn, Adam; Becker, Claude; Bossdorf, Oliver; Münzbergová, Zuzana; Latzel, Vít (The New phytologist, 2024)
Due to the accelerating climate change, it is crucial to understand how plants adapt to rapid environmental changes. Such adaptation may be mediated by epigenetic mechanisms like DNA methylation, which could heritably alter phenotypes without changing the DNA sequence, especially across clonal generations. However, we are still missing robust evidence of the adaptive potential of DNA methylation in wild clonal populations. Here, we studied genetic, epigenetic and transcriptomic variation of Fragaria vesca, a predominantly clonally reproducing herb. We examined samples from 21 natural populations across three climatically distinct geographic regions, as well as clones of the same individuals grown in a common garden. We found that epigenetic variation was partly associated with climate of origin, particularly in non-CG contexts. Importantly, a large proportion of this variation was heritable across clonal generations. Additionally, a subset of these epigenetic changes affected the expression of genes mainly involved in plant growth and responses to pathogen and abiotic stress. These findings highlight the potential influence of epigenetic changes on phenotypic traits. Our findings indicate that variation in DNA methylation, which can be environmentally inducible and heritable, may enable clonal plant populations to adjust to their environmental conditions even in the absence of genetic adaptation.
Keywords: Plants; Humans; Epigenesis, Genetic; buněčné klony; clonal plant; Phenotype; lidé; adaptation; epigeneze genetická; DNA Methylation; transposons; metylace DNA; Fragaria; Clone Cells; climate change; jahodník; environmentally induced epigenetic variation; fenotyp; natural populations; ecological epigenetics; inheritance; rostliny